Resection of Early-Stage Second Primary Non-small Cell Lung Cancer After Small Cell Lung Cancer: A Population-Based Study - Zhang, Rusi; Cai, Ling; Wang, Gongming; Wen, Yingsheng; Wang, Fang; Zhou, Ningning; Zhang, Xuewen; Huang, Zirui; Yu, Xiangyang; Xi, Kexing; Yang, Longjun; Zhao, Dechang; et al. (Frontiers in Oncology, 2020)
Introduction: A certain number of small cell lung cancer (SCLC) patients become long-term survivors after treatment, and they are at high risk for developing a second primary malignancy, including non-small cell lung cancer (NSCLC). However, the optimal management of early-stage NSCLC secondary to SCLC remains unknown. This study aims to evaluate the survival benefits of surgery in these patients. Methods: Patients with early-stage NSCLC secondary to SCLC were identified from the Surveillance, Epidemiology, and End Results database. Patients were balanced with propensity score matching (PSM). Overall survival (OS) and lung cancer-specific survival (CSS) were compared between non-surgery group and surgery group with the Kaplan-Meier method and Cox multivariate regressions. Results: A total of 228 patients with early-stage NSCLC secondary to SCLC were identified. Surgery was associated with significantly improved OS and CSS in the multivariate Cox regression analysis (OS, 5-year survival: 41.2% versus 11.6%, HR: 0.42, 95% CI: 0.31-0.59, P< 0.01; CSS, 5-year survival: 46.8% versus 24.3%, HR: 0.53, 95% CI: 0.37-0.75, P< 0.01). However, no statistically significant survival difference was found between sublobar resection and lobectomy (OS, 5-year survival: 41.0% versus 45.3%, P=0.73; CSS, 5-year survival: 43.5% versus 54.1%, P=0.49). After 1:1 PSM, 162 patients were selected for further analysis, and surgery continued to demonstrate superior survival (OS, 5-year survival: 44.2% versus 7.2%, HR: 0.48, 95% CI: 0.33-0.70, P< 0.01; CSS, 5-year survival: 48.0% versus 20.6%, HR: 0.44, 95% CI: 0.42-0.97, P= 0.03). Conclusion: The resection of early stage NSCLC secondary to SCLC led to significantly improved OS and CSS, and therefore should be considered whenever possible. Nevertheless, further randomized controlled trials are warranted to investigate the safety and effect of surgery in these patients.